The Strategic Relationship Between Space and Customers’ Brand Experience at Exclusive Books - Simmonds, Brendon Shane (The IIE, 2019)
The underlying theme of this small-scale research study is the way in which atmospherics emotionally influence the brand experience construct within the consumption space. Customers’ in-store retail experience has become a fundamental differentiator for brands and their product offerings. This exploratory study used a qualitative research approach to assess how the layout and design considerations of two alternative spaces under the Exclusive Books brand contribute to customer experience. Exclusive Books was selected as a case study because the brand has recently undergone a shift in its retail strategy; the new strategy is reflected in certain of its stores but not others, which provides a unique opportunity for comparison. Observational research was conducted at the brand’s Hyde Park and Gateway stores, and information was also collected through personal interviews and a group interview. The meaningful findings emerging from this study can help to advance the exciting body of knowledge relating to atmospherics in general, and they may also be insightful for Exclusive Books in particular. It was concluded that, in contrast with the flagship store in Hyde Park, the brand’s Gateway store falls short of providing the intended customer experience. There appears to be a disconnect between how the Exclusive Books retail experience is envisaged internally (by the brand) and how it is perceived externally (by the customer) at the Gateway store.
Keywords: Brand; Space planning; Brand experience; Atmospherics; Retail strategy; Environmental psychology